2014
DOI: 10.1080/17439884.2013.878353
|View full text |Cite
|
Sign up to set email alerts
|

Understanding students' use and value of technology for learning

Abstract: Despite significant research in the field of educational technology, there is still much we do not fully understand about students' experiences with technology. This article proposes that research in the field of educational technology would benefit from a sociological framing that pays attention to the understandings and lives of learners. Within a broader study that aimed to investigate students' use and value of technologies guided by Bourdieu's sociological theory, this article reports on qualitative embed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 26 publications
5
48
0
Order By: Relevance
“…Another important perspective that is raised by this case study is that several pupils say they learn better by writing in longhand than on a keyboard when taking notes from a lesson. These findings are supported by researchers such as Beckman, Bennett and Lockyer (2014), James and Engelhart (2012) and Mueller and Oppenheimer (2014). More research is needed here, not least because an increasing number of municipalities have been providing tablets for their pupils from the very first year of school.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Another important perspective that is raised by this case study is that several pupils say they learn better by writing in longhand than on a keyboard when taking notes from a lesson. These findings are supported by researchers such as Beckman, Bennett and Lockyer (2014), James and Engelhart (2012) and Mueller and Oppenheimer (2014). More research is needed here, not least because an increasing number of municipalities have been providing tablets for their pupils from the very first year of school.…”
Section: Resultssupporting
confidence: 73%
“…These findings are also confirmed by other researchers (Fisher, Lucas and Galstyan, 2013;Burden, Hopkins, Male, Martin and Trale, 2012;Hultin and Westman 2013;Beckman, Bennett and Lockyer, 2014) who show that pupils use technology far more often after receiving a personal digital tool than when they have had to stick to the school classroom or computer lab. Teachers did the same when they were also able to use a range of different technologies to present teaching content, such as different tablet apps or a smart board.…”
Section: Literature Reviewsupporting
confidence: 79%
See 2 more Smart Citations
“…For example, Brill and Park (2008) argue that emerging technologies such as augmented reality, virtual reality and mobile technologies make ubiquitous learning and engaged learning possible. However, researchers struggle to find concrete evidence to prove this proposition (Beckman, Bennett, & Lockyer, 2014). Some authors have drawn upon these studies and concluded that despite the technological revolution, the nature of university teaching and learning remains unchanged (Henderson et al, 2015).…”
Section: Norms: Ict For Learning and Teachingmentioning
confidence: 99%